Pencurian dan Watak Kriminal Dalam Perspektif Psikologi Kriminal - Kinanti, Safira Putri; Levia, Nazwa Alva; Puspita, Vani; Hilmi, Adikana Rusyda; Hermita, Zaky Eka; Supriyadi, Tugimin (Media Hukum Indonesia (MHI), 2025)
Theft and Criminal Personality in the Perspective of Criminal Psychology discusses the phenomenon of theft as one of the most common and widespread crimes in Indonesian society, both directly affecting victims and indirectly impacting the social environment. Through a literature review approach, this journal highlights that theft is not merely an illegal act but also a manifestation of complex psychological conditions in the perpetrator, influenced by the interaction between internal factors such as personality, cognitive distortions, harmful childhood experiences, and external factors such as economic conditions, social environment, peer pressure, and culture. In addition to examining the driving factors and negative impacts of theft, this journal emphasizes the importance of understanding the characteristics of perpetrators from a criminal psychology perspective to support prevention, rehabilitation, and law enforcement efforts, thereby aiming to reduce crime rates and enhance community safety.